2020
DOI: 10.1002/vms3.271
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Leptospira serogroups in buffaloes from the Brazilian Amazon

Abstract: Although Brazil has one of the largest buffalo populations in the Americas, buffalo leptospirosis is still poorly explored when compared to that in bovines; thus, the aim of this research was to carry out a large serological study for leptospirosis in this species in the Brazilian Amazon. For this, we collected 1,405 serum samples from buffaloes raised in the Amazon delta region, which is considered a major area of buffalo production in Brazil. The test used was a microscopic agglutination test (MAT) adopting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The other study by employing three serovars (Copenhageni, Icterohaemorrhagiae, and Lai) representing the Icterohaemorrhagiae serogroup and two serovars (Kaup and Tarassovi) representing Tarassovi serogroup in MAT with endpoint titration of cattle serum samples from different geographical locations of India revealed that there was 1-2-fold titer variation on the reactivity of different homologous serovars within specific serogroup (unpublished data). A similar observation was also earlier reported from other endemic countries[34].…”
supporting
confidence: 92%
“…The other study by employing three serovars (Copenhageni, Icterohaemorrhagiae, and Lai) representing the Icterohaemorrhagiae serogroup and two serovars (Kaup and Tarassovi) representing Tarassovi serogroup in MAT with endpoint titration of cattle serum samples from different geographical locations of India revealed that there was 1-2-fold titer variation on the reactivity of different homologous serovars within specific serogroup (unpublished data). A similar observation was also earlier reported from other endemic countries[34].…”
supporting
confidence: 92%
“…Despite in the literature there are no reports of evaluate the effectiveness of the ranking technique in a controlled way, when the infectious serogroup is known (experimental inoculation), this technique were used in MAT serology for random herds of cattle, buffaloes, sheep, horses and other species (5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…First, it is worth noting that the ranking technique, when used, does not negate any sample that was reactive for at least one antigen of the MAT panel, regardless of the titer found, and if there was a tie between antigens from different serogroups, the sample remains positive for leptospirosis and can be considered for calculating the general prevalence of the disease within a herd; however, it is not possible to predict the most likely infecting serogroup for this sample, so it is disregarded only to stipulate the serogroups prevalent in a herd (5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations